A Study to Assess the Knowledge and Practice of Anger Management among Adolescents Students in a Selected School, Thrissur with a View to Prepare a Pamphlet. - S. Prasanth, E.; Vargheese, Ancy; H. Athulya, K.; Babu, Babitha; Sebastian, Chanjal; Jiya, N.; G. Karthika, M.; Nazar, Neema (International Journal of Nursing Research, 2023)
Background: Anger is an emotional state that varies in intensity from mild irritation to intense fury and range. Anger can be caused by both external and internal events. The anger management is helps to reduce both emotional feeling and the physiological arousal that anger causes. Hence, the study was undertaken to assess the knowledge and practice of anger management among adolescent students in a selected School, Thrissur with a view to prepare a pamphlet. The objectives of the study were to assess the knowledge and practice regarding anger management among adolescents and find out the association between knowledge and practice on anger management among adolescents with their selected demographic variables. Methods: Data were collected using a structured questionnaire. The design of study was descriptive survey and was conducted over 212 students from St. Joseph Model Higher Secondary School, Kuriachira, Thrissur. The samples were selected by purposive sampling. Results: According to this study, state that the knowledge regarding anger management among adolescents is inadequate (58.49%) as well as practice regarding anger management among adolescents is also moderate (39.25%). Conclusion: The study concluded with that each school gives some attention to the knowledge of practice regarding anger management among adolescents.